An unusual presentation of late-onset Alexander's disease with slow orthostatic tremor and a novel GFAP variant. Issue 5 (2nd November 2018) - Stitt, Derek W.; Gavrilova, Ralitza; Watson, Robert; Hassan, Anhar
ABSTRACT: Alexander disease (AxD) is a leukodystrophy, described in infantile, juvenile and adult onset forms, due to mutations in the glial fibrillary acid protein (GFAP) gene. Adult-onset AxD (AOAD) has a range of clinical and radiographic phenotypes with the oldest reported onset in the seventh decade.We report a case of AOAD, with onset in the eighth decade, presenting with slow variant orthostatic tremor, which has not been previously described. Genetic analysis revealed a GFAP variant (c.1158C>A) that has not been previously reported. Our case serves to expand the diagnostic spectrum of AOAD both clinically and genetically.